2020
DOI: 10.1021/acs.energyfuels.0c03327
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic Fracture Formation and Distribution in Ultradeep Marine Carbonate Gas Reservoirs: A Case Study of the Maokou Formation in the Jiulongshan Gas Field, Sichuan Basin, Southwest China

Abstract: Tectonic fractures are the key factors affecting hydrocarbon migration and accumulation in ultradeep marine carbonate gas reservoirs. Taking the Maokou Formation in the Jiulongshan Gas Field as an example, tectonic fracture formation and distribution are quantitatively characterized by the outcrops, cores, Fullbore Formation MicroImager (FMI) imaging logging, acoustic emission experiments, fluid inclusion experiments, and burial–thermal evolution history analysis. The formation stage of the tectonic fractures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 46 publications
0
48
0
Order By: Relevance
“…Fractures are important reservoir spaces and migration channels of shale gas, playing an important role in the accumulation, preservation, exploration, and development of shale gas (Li et al, 2019c;Li et al, 2020;Li H. et al, 2021;Li 2021). Investigation of the Lower Paleozoic marine shale gas in the Sichuan Basin and its surrounding areas shows that marine shale has a good material foundation, and gas-bearing can almost be observed in each drilling.…”
Section: Physical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractures are important reservoir spaces and migration channels of shale gas, playing an important role in the accumulation, preservation, exploration, and development of shale gas (Li et al, 2019c;Li et al, 2020;Li H. et al, 2021;Li 2021). Investigation of the Lower Paleozoic marine shale gas in the Sichuan Basin and its surrounding areas shows that marine shale has a good material foundation, and gas-bearing can almost be observed in each drilling.…”
Section: Physical Characteristicsmentioning
confidence: 99%
“…et al, 2020Xu F. S. et al, 2021;Xi et al, 2021a, Xi et al, 2021b. Previous studies have made great progress in understanding the geological characteristics of shale reservoirs; defined the geochemical characteristics, mineralogical characteristics, and reservoir space characteristics of the reservoirs; found that the sedimentary environment, organic matter (OM), clay minerals, brittle minerals, and fractures are the main controlling factors of shale reservoir yields; and formed a comprehensive research system for shale reservoirs (Chen et al, 2016;Li et al, 2019c;Chen S. L. et al, 2020;Li et al, 2020;Liu et al, 2020;Chen et al, 2021a;Chen et al, 2021b;Liu J. et al, 2021;Sun, 2021). However, these research results and conclusions apply mainly to shallow shale gas with a burial depth of less than 3,500 m. Due to the influence of sedimentation, diagenesis, and tectonism, deep shale gas reservoirs have higher contents of brittle minerals, more developed natural fractures, and more complex pore evolution, resulting in different shale geological characteristics and controlling factors for shale gas enrichment and yield (Yin et al, 2019;Chen F. et al, 2020;Chai et al, 2020;Xu and Gao, 2020;Yin and Wu, 2020;Zhou et al, 2020;Song et al, 2021;Tabatabaei 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The collection cost of conventional logging data is much cheaper than other data, so it is widely used in reservoir exploration and evaluation (Jiang et al, 2017;Liu et al, 2019;Santosh and Feng., 2020;Yoshida and Santosh., 2020;He et al, 2021;Huang et al, 2021). However, the logging response is a comprehensive reflection of the various characteristics of the rock, and it is easily affected by factors such as fillings, mud, and dissolution (Mardia et al, 2007;Laubach et al, 2009;Sun et al, 2014;Hu et al, 2020;Li et al, 2020;Kang., 2021). Therefore, it is very difficult to directly use conventional logging curves to identify fractures.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of pyrite developed in shale to the pore system is now widely accepted (Li et al, 2019;Li et al, 2020;Liu et al, 2022), but there are still some disputes about its porosity development degree and the importance of pores related to pyrite. The contribution of pore development characteristics related to the pyrite of a shale reservoir cannot be quantified .…”
Section: Introductionmentioning
confidence: 99%